Manajemen Pembelajaran Inovatif: Integrasi Pendidikan Karakter pada Anak Usia Dini - Risnajayanti (LEMBAGA PENELITIAN & PENGABDIAN MASYARAKAT UNIVERSITAS SINGAPERBANGSA KARAWANG, 2023)
This study aims to summarize and analyze innovative learning management strategies in forming positive character at the stage of early childhood development. The study adopts a literature study approach by exploring key concepts and relevant best practices. The results of literature analysis show that innovative approaches in learning management open up opportunities to integrate character values in the early childhood curriculum. Teachers as educational leaders, have a central role in implementing creative and in-depth learning strategies. The implementation of learning programs involves the use of innovative methods, collaborative projects, and the use of supporting literature that is characteristic. Although the study is literatureary, the synthesis of information from multiple sources proves that character education in early childhood can be effectively integrated through innovative approaches in learning management. The implications of these findings lead to the development of responsive curricula and teacher resources that focus on aspects of character.